Appointment of Acting Regional Heads by The Central Government: Analysis of Authority and Principles of Local Democracy - Lumba Agung Masben; Achmad Edi Subiyanto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The appointment of an Acting Regional Head by the Central Government during the transition period of the 2024 National Simultaneous Regional Elections has sparked constitutional controversy regarding government authority and alignment with the principles of local democracy and decentralization. This study aims to examine the legal construction of the Central Government's authority in appointing Acting Regional Heads. In addition, this study also seeks to evaluate the suitability of this practice with the principles of democracy and decentralization as stipulated in the 1945 Constitution of the Republic of Indonesia. The method used in this study is a normative legal research method, by applying a statutory approach and a conceptual approach. The legal sources that are the object of analysis include the 1945 Constitution, Law No. 10 of 2016, Law No. 23 of 2014, and Regulation of the Minister of Home Affairs No. 4 of 2023, Constitutional Court decisions, and scientific literature related to the theory of authority and democracy. The results of the study indicate that the authority of the Central Government in appointing Acting Regional Heads is formally attributive and meets the principle of legality. However, the regulatory framework still leaves serious issues related to the limits of authority, selection mechanisms, accountability, and minimal participation by the Regional People's Representative Council (DPRD) and local communities. This situation creates a deficit in democratic legitimacy and a tendency towards recentralization, which has the potential to undermine the principle of regional autonomy. This study concludes that the appointment of Acting Regional Heads is formally constitutional but problematic from a democratic and decentralized perspective, necessitating a reconstruction of the appointment mechanism to align with the principles of local democracy and a democratic state based on the rule of law.